DAMPAK KINERJA LINGKUNGAN, KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN PUBLIK, LEVERAGE, UKURAN PERUSAHAAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNGJAWAB SOSIAL - Erva Wartina, Prima Apriweni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
The company's obligation is not only to seek profit but also to do social responsibility (CSR). For companies that use natural resources in operational activities, it is appropriate to conduct CSR activities and disclose them in annual reports. This study aims to determine whether environmental performance, institutional and public share ownership, leverage, size and growth of the company affect the disclosure of CSR. Sample of the research is 25 agricultural and mining companies listed in Indonesia Stock Exchange (IDX) over a period of 4 years (2013-2016). While the analysis to be used are equality coefficient test, classical assumption test, multiple linear regression analysis, and statistic test.The results of this study concluded there is sufficient evidence on the variables of environmental performance and firm size affecting CSR disclosure, whereas in institutional ownership variables, public ownership, leverage, and corporate growth there is not enough evidence of these variables affecting CSR disclosure.Â Keyword: CSR Disclosure, Institutional Ownership, Public Ownership, Leverage, Size Firm